2007
DOI: 10.1892/0891-6640(2007)21[238:dcandi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Cardiac and Noncardiac Dyspnea in 48 Dogs Using Plasma Atrial Natriuretic Factor, B-type Natriuretic Factor, Endothelin, and Cardiac Troponin-i

Abstract: Plasma NT-proANP, BNP, and ET-1, but not cTnI, appear useful for distinguishing between dogs with cardiac and noncardiac causes of dyspnea, with plasma NT-proANP having the highest sensitivity (95.5%) and specificity (84.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 21 publications
1
69
2
8
Order By: Relevance
“…This indicated that plasma [NT‐proBNP] was useful and accurate within the context of 81% specificity and 73% sensitivity, using a 2,447 pmol/L cut‐off value. Other studies of dogs have reported relatively similar natriuretic peptide sensitivity and specificity with respective values ranging from 85 to 82.4%,28 86.4 to 80.8%,4 90 to 78%,5 and 85.5 to 81.3% 8. Our study confirmed the utility of measuring plasma [NT‐proBNP] to help discriminate cardiac from noncardiac causes of dyspnea, consistent with earlier reports 4, 5, 6, 7, 8, 27, 28…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that plasma [NT‐proBNP] was useful and accurate within the context of 81% specificity and 73% sensitivity, using a 2,447 pmol/L cut‐off value. Other studies of dogs have reported relatively similar natriuretic peptide sensitivity and specificity with respective values ranging from 85 to 82.4%,28 86.4 to 80.8%,4 90 to 78%,5 and 85.5 to 81.3% 8. Our study confirmed the utility of measuring plasma [NT‐proBNP] to help discriminate cardiac from noncardiac causes of dyspnea, consistent with earlier reports 4, 5, 6, 7, 8, 27, 28…”
Section: Discussionsupporting
confidence: 91%
“…Measurement of natriuretic peptides including canine N‐terminal pro‐brain natriuretic peptide concentration ([NT‐proBNP]) provides insights to distinguish cardiac from noncardiac respiratory distress,3, 4, 5, 6, 7, 8 assess heart disease (HD) severity,7, 9, 10, 11 predict onset of CHF,11 provide prognostic information in myxomatous mitral valve disease (MMVD),10, 11, 12, 13, 14 and dilated cardiomyopathy (DCM),15, 16 and help with treatment decisions 17…”
mentioning
confidence: 99%
“…There are breed differences in concentrations of natriuretic peptides and catecholamines in the same healthy dogs 11, 15. Several of these substances are altered in development of cardiac or renal disease and have been investigated as potential biomarkers for disease in dogs 4, 5, 6, 8, 24. A clinically useful test requires an upper reference limit for healthy dogs, and cut‐off values for dogs with subclinical disease or clinical signs of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, increased concentrations of ET‐1 have been found in chronic kidney disease and ET‐1 has been suggested a biomarker of hypertension 6. In one study, plasma concentrations of ET‐1 were twice as high in dogs with congestive heart failure compared to controls,26 and studies indicate that ET‐1 could aid in distinguishing between cardiac and noncardiac causes of dyspnea in dogs 5, 8. ET‐1 has also been suggested an useful predictor of poor prognosis in dogs with dilated cardiomyopathy 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation